2011
DOI: 10.1002/hbm.21076
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network abnormalities in mesial temporal lobe epilepsy: A study combining fMRI and DTI

Abstract: Studies of in mesial temporal lobe epilepsy (mTLE) patients with hippocampal sclerosis (HS) have reported reductions in both functional and structural connectivity between hippocampal structures and adjacent brain regions. However, little is known about the connectivity among the default mode network (DMN) in mTLE. Here, we hypothesized that both functional and structural connectivity within the DMN were disturbed in mTLE. To test this hypothesis, functional magnetic resonance imaging (fMRI) and diffusion tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
237
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(279 citation statements)
references
References 61 publications
(111 reference statements)
30
237
2
Order By: Relevance
“…Of note, fiber tracts in the DMN, such as those connecting pCC to bilateral mTLs [20], and pCC to mPFC [21,22], are also detectable between homologous regions in nonhuman primates using effective tracers, suggesting the effectiveness of in vivo DTI tractography in tracing tracts. Subsequent neuroimaging studies [19] combining DTI tractography and fc-fMRI have confirmed a relationship between functional and anatomical connections within the DMN in agreement with Greicius et al [8], further implying that regions that are connected directly by fiber tracts also have significant functional connections, but the inverse condition need not be true because functional connections might be linked indirectly via multisynaptic connections or more distant cortical regions.…”
Section: Connectivity Within the Default Mode Networksupporting
confidence: 68%
See 1 more Smart Citation
“…Of note, fiber tracts in the DMN, such as those connecting pCC to bilateral mTLs [20], and pCC to mPFC [21,22], are also detectable between homologous regions in nonhuman primates using effective tracers, suggesting the effectiveness of in vivo DTI tractography in tracing tracts. Subsequent neuroimaging studies [19] combining DTI tractography and fc-fMRI have confirmed a relationship between functional and anatomical connections within the DMN in agreement with Greicius et al [8], further implying that regions that are connected directly by fiber tracts also have significant functional connections, but the inverse condition need not be true because functional connections might be linked indirectly via multisynaptic connections or more distant cortical regions.…”
Section: Connectivity Within the Default Mode Networksupporting
confidence: 68%
“…In a resting-state fcfMRI study, Greicius and colleagues [8] found that pCC shows significant functional connectivity with mPFC, inferior parietal cortex, parahippocampal gyrus, and inferior temporal cortex within the DMN in healthy volunteers, and these connections are minimally disrupted during task performance, indicating preservation of DMN functional connectivity across the rest and task conditions. Functional connectivity between pCC/PCUN and mPFC, and pCC/PCUN and mesial temporal cortex within the DMN was detected in both healthy controls and patients with mesial temporal lobe epilepsy, demonstrating the robustness of these relationships in health and disease [19].…”
Section: Connectivity Within the Default Mode Networkmentioning
confidence: 87%
“…Other studies have used different approaches (i.e., ICA, seed‐based connectivity) to explore some specific RSNs such as the DMN [Liao et al, 2011], perceptual [Zhang et al, 2009a], and attention networks [Zhang et al, 2009b]. These studies revealed altered networks, compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed altered networks, compared to controls. The overall activation of DMN in MTLE is apparently reduced, as well as the functional connectivity between its nodes [Liao et al, 2011]. Some of these studies also demonstrated that MTLE affects the attention networks and perceptual networks, resulting in significant abnormal impairment between their regions [Cataldi, et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Using DTI and fMRI, Teipel et al [100] and Greicius et al [101] showed that functional connectivity across the entire DMN is based on a distinct pattern of anatomical connectivity within the cerebral white matter. In addition, some psychiatric diseases, such as schizophrenia [102] , AD [103][104][105] , and epilepsy [106] , also demonstrate a decreased WMM connectivity within the DMN. In a recent review [4] , Hulvershorn et al used a dMRI-derived network to systematically review the dysfunctional connectivity in pediatric MDD.…”
Section: Dmri Network-based Applications In Neuropsychiatric Diseasementioning
confidence: 99%